A universal strategy for the synthesis of porous two-dimensional transition metal oxide nanosheets based on chemical topology transformation - Li, Xiang; Qin, Ziyu; Hu, Xiafen; Zhang, Jian; Wu, Jinjin; Yang, Huimin; Xie, Changsheng; Zeng, Dawen (Science China materials, 2021)
Two-dimensional (2D) transition metal oxides (TMOs) have attracted much attention for various applications, owing to the abundance of active sites, rapid ion transmission speed, and short carrier migration distance. However, the current preparation strategies are usually limited to producing intrinsically layered compounds or sacrificing template. Here, we report a universal strategy for preparing ultrathin porous 2D TMO nanosheets by chemical topological transformation of the corresponding transition metal selenides. We observed that the as-prepared 2D TMO nanosheets not only perfectly inherit the transition metal selenides’ 2D topological structure, but also possess numerous pore structures formed as a way to release the structural stress associated with lattice growth. As a proof of concept, ultrathin porous WO 3 , MoO 3 , and Co 3 O 4 nanosheets were successfully prepared based on the in-situ oxidation of the corresponding ultrathin WSe 2 , MoSe 2 , and Co 0.85 Se, respectively. The outstanding sensing properties and photodetector performance displayed by the as-prepared porous 2D WO 3 nanosheets further indicate the promising prospects of topology transformation for the preparation of porous 2D TMO nanosheets.